The development of automated segmentation for the FTMSK official letters in XML / Muhammad Muhaimin Mohd Isa - Mohd Isa, Muhammad Muhaimin (2005)
The letter document has their own fomiat, which consists of many parts. In order to process the document, the project has developed a prototype to allow the existence of content based document. This is important to divide the document into smaller, recognized labels that are intensive and flexible for managing, editing, and extracting. The target of this thesis is to apply the standard of official letter for the system, as well as to develop the algorithm which will segment the letter documents, and convert to XML documents. The main software used is Visual Basic 6.0. The project was estimated by evaluating the similarity of the contents in letter document and the output of XML document. The prototype is tested by using approach of manual checking. About 20 samples of letters have been tested to verity the prototype efficiency. The result of the experiment shows that 30% of the output can not be viewed due to the runtime en-ors. The findings of the research include the interviews and surveys appointed, the study of related topics and problems firom the internet, books, and other information medium. The data was collected from the FTMSK administration department, and the testing was done manually using researcher's own workstations and hardware.